Tuning experiential activities’ constraints influences student engagement and focus on transversal skills - Isaac, Siara; de Lima, Joelyn; Jalali, Yousef; Rossi, Valentina; Schmid, Samuel; Popescu, Stefan Gabriel; Tozadore, Daniel; Dehler Zufferey, Jessica (Frontiers in Education, 2026)
IntroductionExperiential learning is well-suited for developing transversal skills; however, poor understanding of pedagogical conditions for skill development reduces the contributions of such approaches in engineering education. This paper examines how adjusting the constraints of collaborative design tasks can increase engagement and refine students’ personal development goals.MethodsEighty-five engineering students participated in activities, based on the 3T PLAY framework, that emphasized specific skills. Students evaluated their designs, reported their emotional state, self-assessed their transversal skills, and identified the skills they wanted to develop.ResultsAnalysis showed that the specific constraints of each experiential activity influenced the skills prioritized by students while increasing the specificity of the skills they cited. Students’ evaluation of their design and emotional states show high engagement and potential for eliciting pedagogically relevant emotions for sustainability.DiscussionThe findings indicate adjusting the characteristics of design projects, particularly task constraints, can increase students’ awareness of key transversal skills. Additionally, the results support the use of the proposed micro-experiential learning activity structure to integrate scaffolded support for transversal skill development into engineering courses.